Wozu erinnern? - Engel, Nicolas; Bretting, Johannes (Zeitschrift für Pädagogik, 2024)
The article thematizes Adorno’s request of an ‘Education after Auschwitz’ as an educational problem of the distribution and participation of knowledge. It asks about the organisational and institutional preconditions that create or are capable of destroying the transmission and appropriation of knowledge. From a cultural studies perspective, it is proposed that ‘Education after Auschwitz’ is addressed as a question of how to deal adequately with knowledge in changed constellations of remembrance. For this purpose, the concept of knowledge encounter is defined, with which the necessary formation of a power of resistance can be reformulated as a task of ‘Education after Auschwitz’ in the present.
CRIS-Team Scopus Importer:2024-12-13
Keywords: Education after Auschwitz; Institutionalization; Knowledge Encounter; National Socialism; Remembrance